Regulasi Pemanfaatan Lahan Gambut Dalam Tinjauan Economic Analysis of Law dan Pendekatan Konservasi - Maya Simorangkir (CV. Rayyan Dwi Bharata, 2025)
Government Regulation No. 57 of 2016 on Amendment to Government Regulation No. 71 of 2014 on protection and management of peat ecosystems that substantively emphasizes on sustainable management of peat so there must be a balance of conservation function and aquaculture function, especially on peatlands already already opened and cultivated. Indonesian Peatlands Data that problems related to social and economic aspects will be experienced by many forestry and oil palm business actors including peasants who use peatlands because according to Article 23 paragraph (3) peatlands declared damaged if the groundwater surface in peatland 0.4 meters below the surface of the peat or exposure to pyrite sediments. Currently land for acacia and palm oil plants requires groundwater levels between 0.6-0.8 meters below the surface of the peat. Furthermore, with advances in current technology, the exposure of pyrite sediments can still be used for acacia plants and oil palm. The PP indicates the inconsistency of our peat regulation due to some previous legal products, namely: (i) of the 1945 Constitution of the State of the Republic of Indonesia Article 33 paragraph 3 which states that: